Workshop Pengembangan Modul Pecahan Senilai Berbasis Matematika Realistik Berorientasi HOTS bagi Guru SD - Sutarni, Sri; Utami, Nida Sri; Faiziyah, Nuqthy (Pelita: Jurnal Pengabdian kepada Masyarakat, 2024)
Elementary mathematics learning with an independent curriculum can be carried out well if the learning plan has been prepared well. This means that teachers must be able to organize teaching modules well. This service activity aims to improve the abilities of Madrasah 'Ibtidaiyah Muhammadiyah (MIM) teachers in Kartasura sub-district regarding the development of realistic mathematics-based teaching modules oriented to High Order Thinking Skills (HOTS). The activity was carried out at Madrasah 'Ibtidaiyah Muhammadiyah (MIM) Gonilan. This activity in the form of a workshop was attended by 12 participant that is MIM teachers from Kartasura District. This activity is carried out using lecture methods and also exercises. Based on the results of the final questionnaire of the activity, it can be seen that there was a slight increase in the knowledge of the teachers regarding teaching module material, realistic mathematics, and HOTS.